Developing Bidikmisi Information System - Humaira; Rasyidah; Indri Rahmayuni; Junaldi; Deny Kurniawan (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2020)
Bidikmisi is a scholarship provided by Indonesian Government. This scholarship is for outstanding studentscoming from poor family. The importance of this scholarship is for the sustainability of education inIndonesia and it needs a system to support it. This paper discusses the development of BidikmisiInformation System Web and Android Based. The design tool was by using Unified Modelling Language(UML). The software equipment implementation was web based using Lavarel framework aiming forregistration data validation. While android application is aimed for the supporting aid when visitation. Theresults of the examination obtain 45,86% data of the registrants are invalid.